Priming with high and low respiratory allergen dose induces differential CD4+ T helper type 2 cells and IgE/IgG1 antibody responses in mice. Issue 2 (3rd April 2017) - Furuhashi, Kazuki; Chua, Yen L.; Wong, Kenneth H. S.; Zhou, Qian; Lee, Debbie C. P.; Liong, Ka H.; Teo, Guo H.; Hutchinson, Paul E.; Kemeny, David M.
Summary: Sensitization of allergic patients normally takes place over several years and is the result of repeated exposure to low levels of allergen. Most mouse asthma models use a high dose of allergen administered over a short period. We have investigated the role of dose in the immune response to an inhaled respiratory allergen ( Blomia tropicalis ). We observed the effect of priming dose on the allergic response in mice intranasally immunized with low (0·5 μg) and high (50 μg) doses of B. tropicalis extract and killed 1 day after the last challenge. For both doses of allergen, T helper type 2 (Th2) cells and Th2 cytokines were evident as well as eosinophilic inflammation accompanied by mucus hyper‐secretion. By contrast, IgE and IgG1 antibody responses were normally only detected at high‐dose priming. To investigate the mechanism for these effects, we found group 2 innate lymphoid cells (ILC2s) were increased 48 hr after challenge in the low‐dose‐treated but not the high‐dose‐treated mice. Furthermore, we determined whether repeated low‐dose exposure with different priming protocols could induce an antibody response. Repeated low‐dose exposure to 0·5 μg three times weekly for 4 weeks (cumulative 6 μg) had the same effect as a shorter high‐dose exposure (cumulative 80 μg) and increasing cumulative dose induced antibody responses. These data indicate that low doses of allergen are sufficient to prime Th2 cells and ILC2s, but insufficient to induce antibody responses. Cumulative exposure to small amounts of allergen induces both Th2 and antibody responses and may better reflect natural sensitization. Abstract : Low‐dose priming induced a comparable T helper type 2 (Th2) response to high‐dose priming, but failed to elicit specific IgE/IgG1 responses. Repeated low‐dose exposure produced the same features of Th2 cells and IgE/IgG1 antibodies to high‐dose priming and so is closer to the way that allergic patients are sensitized.